Overview on diabetic foot: a dangerous, but still orphan, disease. (9th March 2015) - Dalla Paola, Luca; Carone, Anna; Vasilache, Lucian; Pattavina, Marco
Abstract: Diabetic foot disease is a major health problem that concerns 15% of the 200 million patients with diabetes worldwide. More than 60% of non-traumatic amputations in the western world are performed in the diabetic population. Many patients who undergo an amputation have a history of ulceration. Treatment of foot complications is one of the main items of consumption of economic and health resources in diabetic patients. Over recent years, knowledge about the physiopathological pathways of this complication has increased significantly, together with improvements in diagnostic techniques and, above all, the establishment of a standardized conservative therapeutic approach, which allows limb salvage in a high percentage of cases. An important prelude to diabetic foot treatment is the differential diagnosis between neuropathic and neuroischaemic foot, which is essential for effective treatment. Ulceration in neuropathic foot is due to biomechanical stress and high pressure, which involves the plantar surface of the toes and metatarsal heads. In the diabetic population, peripheral vascular disease (PVD) is the main risk factor for amputation. In diabetic patients, PVD is mostly distal, but often fully involves the femoral, popliteal, and tibial vessels. It can be successfully treated with either open surgical or endovascular procedures. If PVD is ignored, surgical treatment of the lesion cannot be successful. Infection is a serious complication of diabetic foot, especially when neuroischaemic: phlegmon and necrotizing fascitis are not only limb-threatening problems, but also life-threatening. In this case, emergency surgery is needed. The aim of this review is to describe the therapeutic strategies for the various types of diabetic foot syndrome.